Successful multimodality management of severe pulmonary arterial hypertension during pregnancy with VA-ECMO and atrial septostomy using stent. Issue 12 (2nd December 2019) - Phoophiboon, Vorakamol; Jaimchariyatam, Nattapong; Srimahachota, Suphot; Sirinawin, Chayatat
Abstract : A 30-year-old Thai woman (gravida 1, para 0) at 33 weeks gestation was referred to our hospital due to acute right ventricular failure. Pulmonary vasodilators were gradually administered before delivery. On the verge of sudden postpartum cardiac circulation collapse, she was resuscitated with veno-arterial extracorporeal membrane oxygenation (VA-ECMO). Abdominal compartment syndrome was developed in the early period of the mechanical support. Knowledge of pathophysiology about pulmonary arterial hypertension during pregnancy was applied. Atrial septostomy was the effective procedure for discontinuing mechanical support (VA-ECMO) corresponding to the suitable timing for maximal effect of pulmonary vasodilators. The patient and her child were safe and discharged in 2 months after the admission.